Human Resources Development and Management of The Open Distance Learning In The Seashore South of East Java Province, Indonesia (Case Study of Jember Regency Open Distance Learning Services): Human Resources Development, Management Development, and Open Distance Learning - Joko Isdianto (STISOSPOL WASKITA DHARMA, 2020)
When technology has helped all people all around the world, we can say that people always depend on it. Technology always changes into the advanced ways but people seldom make a change, The all helpings from the advanced technologies have been increasing day by day. The days have become clearer than before because all people get their needs with the advanced technology, such as computerized element for teaching and learning program, computerized for writing, calculating, thinking, hardware for making the vehicles, for making airplanes, for making kitchen set, etc. Also, They do so many things with the capacities of computerized hardware and equipment maximally. For teaching and learning programs at Jember Open Distance learning, has been spread out all over East Java Province, including seashore south of east java province as jember work area. At Open Distance Learning of Jember, also use high technologies to control all activities from all fields, such as academic fields, registration fields, documentation fields and learning teaching fields. When we want to spread out all the learning programs at the seashore around the Jember work area, we also use the high technology to improve data, to make promotion socialization programs, to make much more training and learning for our students. Beside, Study and learning teaching activities have been easier than before, with our learning teaching program applications, even in the seashore south of east java province. At this seashore area, All students can use this hardware and software maximally, human resources management and internet networking management. Both of them, They have their own role in the part for increasing the work capacities of Open University in all towns. Discussing all the problems within the services process at Open Distance Learning Unit of Jember, we remind about the obstacles with Human Resources and capabilities of the services system. Also, The knowledge of Open University working system is needed for all officers of Open University, at the central and region. It’s all about the services management, internal and external system reforms, Including efficiency, and effectiveness and budgeting efficiency. Open distance learning is the most quickly developing fields of instruction nowadays and it has a generous effect on all training conveyance frameworks. Long Distance framework developing quick as a result of the improvement of Internet-based data advances, and specifically the World Wide Web. The idea of Long Distance training originated from thought where the students and the educators cannot be in a classroom and they ought to be isolated by some geological issues or might be they can't approach each other to make simple the whole instruction framework. It is routed to a wide scope of potential accomplices, governments, intergovernmental and non-legislative associations, specific establishments, affiliations, modern corporations, telecommunication organizations, and others intrigued by this field, to look for their co-activity in meeting the present dire instruction and preparing needs, through open and separation learning.